Sosialisasi Membangun Kreativitas Siswa SMPN 17 Padang Pada Era Digital - Selvi Zola Fenia; Nia Nadila; Tri Ayu Parwati (Jurnal Pengabdian Masyarakat Dharma Andalas, 2023)
Humans can never be separated from technology. Almost all activities carried out by technology-based people. Technological developments bring a change to life man. One of them is in the field of education. The purpose of the Community Service activity This community is to build the creativity of students at SMP N 17 Padang in the digital era with utilize technology in the learning process. The method used in Community Service activities To this community is by providing socialization to students how to do it build and develop creativity by utilizing existing technology. Know the features from creativity to be able to work and create something that did not exist before. This activity was carried out at SMP N 17 Padang in July 2023.